2019
DOI: 10.1002/cjoc.201800555
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐promoted Intramolecular Photoenolization/Diels–Alder Reaction to Construct Polycyclic Terpenoids: Formal Synthesis of Mycoleptodiscin A

Abstract: Summary of main observation and conclusion A titanium‐promoted intramolecular photoenolization/Diels–Alder (PEDA) reaction was developed to construct the core skeleton of aromatic polycyclic terpenoids bearing an all‐carbon quaternary center on the benzylic position. Titanium(IV) isopropoxide [Ti(Oi‐Pr)4] plays a key role during the photo cycloaddition, which may help to accelerate the interaction between dienophile and the stereo‐hindered diene species as well as control the diastereoselectivity. This photoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…76a The first total synthesis of mycoleptodiscin A was published in 2015, 76b while later, in 2019, Xue et al reported a formal synthesis of the natural product by starting from (+)-sclareolide and utilizing a Ti(IV)-promoted photoenolization with subsequent intramolecular cyclization as the key step (Scheme 54). 77…”
Section: Formal Synthesis Of Mycoleptodiscin Amentioning
confidence: 99%
“…76a The first total synthesis of mycoleptodiscin A was published in 2015, 76b while later, in 2019, Xue et al reported a formal synthesis of the natural product by starting from (+)-sclareolide and utilizing a Ti(IV)-promoted photoenolization with subsequent intramolecular cyclization as the key step (Scheme 54). 77…”
Section: Formal Synthesis Of Mycoleptodiscin Amentioning
confidence: 99%
“…Recently, the Gao group reported the use of a Lewis acid to facilitate the Diels–Alder phase of the process, permitting the first catalytic enantioselective processes. This methodology has been applied at an early stage in the total syntheses of oncocalyxone B, mycloeptodiscin A, , (+)-xestoquinone, and (+)-adociaquinones A/B . The robust nature of the PEDA sequence has also permitted application outside of target-based synthesis such as photoligation, photoremovable protecting groups, and photoactivated fragrances …”
Section: Introductionmentioning
confidence: 99%
“…Our synthesis commenced with the key asymmetric photoenolization/Diels–Alder (APEDA) reaction between fragments 15 and 16 , which could be efficiently prepared in decagram scale (see details in the Supporting Information). Recently, we found that a Lewis acid plays a key role in the PEDA reaction, which helps to activate the inert dienophiles and control the diastereoselectivity. However, catalytic asymmetric PEDA reaction using sterically hindered multiple substituted olefins as dienophiles has been elusive. , We speculated that a bifunctional catalyst might meet the challenges of asymmetric UV-light initiated cycloaddition. A combination of Lewis acid [Ti­(O i -Pr) 4 ] and a chiral ligand was designed to control the enantioselectivity and suppress the background reaction.…”
mentioning
confidence: 99%
“…to 95%. We envisioned that a chiral dinuclear species Ti-TADDOLate 17 was formed as a bifunctional catalyst, and the cycloaddition occurred through an endo direction in the chiral environments. , This is the first application of the APEDA reaction in total synthesis to construct the vicinal quaternary stereocenters, which is a synthetic challenge in organic synthesis.…”
mentioning
confidence: 99%